1988
DOI: 10.1099/0022-1317-69-5-1117
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of in vitro Translation of Bean Yellow Mosaic Virus RNA: Inhibition of Proteolytic Processing by Antiserum to the 49K Nuclear Inclusion Protein

Abstract: SUMMARYIn vitro translation of bean yellow mosaic virus (BYMV) RNA in rabbit reticulocyte lysate without dithiothreitol (DTT) resulted in the accumulation of high Mr products. These were readily processed to low Mr mature proteins after the addition of DTT followed by a 2 h incubation. Immunoprecipitation analyses of the partially processed high Mr products with antisera to the 49K and 54K nuclear inclusion (NI) proteins, cylindrical inclusion (CI) protein, tobacco vein mottling virus helper component (HC) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Many isolates of BYMV are recognized and have been divided into a BYMV subgroup along with the closely related potyviruses on the basis of their overlapping host ranges and common biological and immunological properties (Guyatt et al, 1996; Randles et al, 1980 of linear, positive-sense, single-stranded ribonucleic acid (ssRNA), about 9.6 kb in size, which has a poly (A) tract at the 3'-end (Shukla et al, 1994). Based on the results of some studies (Chang et al, 1988a;1988b), BYMV genome is initially translated into a single polyprotein which is processed by viral-encoded proteases into its mature functional products. This gene expression strategy is defined as a general scheme of potyviral gene expression based on the analyses of other members in the genus Potyvirus (Allison et al, 1986;Dougherty et al, 1989;Shukla et al, 1994;Vance et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Many isolates of BYMV are recognized and have been divided into a BYMV subgroup along with the closely related potyviruses on the basis of their overlapping host ranges and common biological and immunological properties (Guyatt et al, 1996; Randles et al, 1980 of linear, positive-sense, single-stranded ribonucleic acid (ssRNA), about 9.6 kb in size, which has a poly (A) tract at the 3'-end (Shukla et al, 1994). Based on the results of some studies (Chang et al, 1988a;1988b), BYMV genome is initially translated into a single polyprotein which is processed by viral-encoded proteases into its mature functional products. This gene expression strategy is defined as a general scheme of potyviral gene expression based on the analyses of other members in the genus Potyvirus (Allison et al, 1986;Dougherty et al, 1989;Shukla et al, 1994;Vance et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Potyviral RNA is translated into a polyprotein containing between 3005 (TVMV) and 3206 (PSbMV) amino acids. This polyprotein is proteolytically processed into at least eight mature proteins by three virusencoded proteinases, the N-terminal (P1) protein (Verchot et al, 1991), the helper component-proteinase (HC-Pro) (Carrington et al, 1989;Carrington & Herndon, 1992), which is also involved in aphid transmissibility, and the nuclear inclusion a protein (NIa-Pro) (Carrington & Dougherty, 1987;Chang et al, 1988;Hellmann et aL, 1988;Garcia et al, 1989;Ghabrial et al, 1990). Other viral proteins with known function are the cytoplasmic inclusion protein (CI) which displays an RNA-dependent ATPase activity characteristic of RNA helicases ; VPg which has been determined to constitute the N-terminal domain of NIa-Pro (Murphy et al, 1990;Dougherty & Parks, 1991), the nuclear inclusion b protein (NIb) thought to be the core replicase (Dougherty & Carrington, 1988) and the capsid protein (CP) (Shukla & Ward, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…10 kb (Hollings & Brunt, 1981). Several investigations have demonstrated that post-translational proteolytic processing of polyproteins is the mechanism of potyviral genome expression (Dougherty et al, 1985;Allison et aL, 1986;Carrington & Dougherty, 1987;Hellmann et al, 1988 ;Chang et al, 1988). The positions of functional virus proteins in the polyprotein have been proposed for tobacco vein mottling virus (TVMV) (Domier et al, 1986), helper component protein (HC), cylindrical inclusion protein (CI), two nuclear inclusion proteins (NIa and NI0 and the coat protein (CP).…”
Section: Introductionmentioning
confidence: 99%